2020
DOI: 10.3390/su122410303
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing the Purchase Intention of Autonomous Cars

Abstract: Even though autonomous cars have not yet crossed into the mainstream car market, their adoption seems inevitable, but not much is known about the purchasing intention of ACs and potential influences on it. To better understand the influences of various factors on purchasing intentions of autonomous cars, research using bibliometrics, an online survey and SEM modelling was performed. Based on an analysis of previous research work and the unified theory of acceptance of technology, an empirical model was produce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…According to the Chinese seventh census data released in 2021, people aged 60 and above account for 18.7% of the total population, and those aged 65 and above account for 13.5% of the total population [79]. However, there is a significant difference between the older and younger generations in their attitude towards emerging scientific and technological products [80]. Therefore, the data of this study may not fully reflect the attitude and opinion of the older generation towards the residential photovoltaic system.…”
Section: Discussionmentioning
confidence: 99%
“…According to the Chinese seventh census data released in 2021, people aged 60 and above account for 18.7% of the total population, and those aged 65 and above account for 13.5% of the total population [79]. However, there is a significant difference between the older and younger generations in their attitude towards emerging scientific and technological products [80]. Therefore, the data of this study may not fully reflect the attitude and opinion of the older generation towards the residential photovoltaic system.…”
Section: Discussionmentioning
confidence: 99%
“…Initially, safety is the most serious consideration [2,3]. According to the research on the influencing factors of consumers' purchase intention to ACs which held by Topolšek et al in 2020 demonstrated that in addition to the factors related to the automobile product itself, the characteristics of consumers themselves, such as age and education level, will also affect the purchase intention [4]. Secondly, Barry in 2017 found that there was also a significant connection existing between social influence and purchase intention when a product was used publicly [5].…”
Section: Influencing Factor For Purchase Intentionmentioning
confidence: 99%
“…In addition to ethics, it is important to address the contradiction between public and individual needs in automated vehicle decisions. Current studies have shown that factors such as age, gender, education, national culture, anxiety, vehicle safety, and traffic accident rates influence AVs decision-making [ 20 , 21 ]. In order to obtain public ideas, Edmond et al [ 22 ] designed an online moral machine experiment platform that collected 40 million decision outcomes from millions of people in 233 countries and regions.…”
Section: Literature Reviewmentioning
confidence: 99%